A systematic review of the clinical practice guidelines for the assessment, management and treatment of eating disorders during the perinatal period - Chantelle Ecob; Debbie M. Smith; Zoe Tsivos; Noora Hossain; Sarah Peters (BMC Pregnancy and Childbirth)
Abstract Background Eating disorders during the perinatal period can pose significant risks to both the mother and the baby. Clinical practice guidelines include statements of expected practice intending to improve effectiveness and quality of care within health care services. This systematic review aimed to identify and synthesise current clinical practice guideline recommendations on the assessment, management and treatment of eating disorders during the perinatal period. Methods Three bibliographic databases and five guideline repository databases were searched alongside the grey literature. Guidelines were screened against eligibility criteria and recommendations for the assessment, management or treatment of eating disorders during the perinatal period were extracted. All included guidelines were assessed for quality using the AGREE-II tool. Recommendations were analysed and summarised using narrative synthesis. Results From the 242 records screened, 17 met inclusion criteria. Guideline quality ranged from three out of seven to seven out of seven. Six overall recommendations were formed from the narrative synthesis of data: 1) Early detection: recognising the signs and symptoms, 2) Assessment and screening: a three-pronged approach, 3) Educating and supporting the mother: the importance of knowledge, 4) Cross-system collaboration, 5) Psychological, pharmacological and medical treatment, and 6) Continued monitoring. Conclusion Perinatal eating disorder guideline recommendations were fairly consistent but showed considerable variability in quality and depth of recommendations. Recommendations require further contextualisation, to allow them to be operationalised and implemented within services. The review findings provide an initial framework for health care professionals responsible for supporting women with eating disorders during the perinatal period, and have several implications for policy, service delivery and health outcomes for women and their families.